Collaborative Governance in Reduce the Impact of The Spread of The Covid-19 Pandemic on the Industrial Sector in Karawang Regency - Zahra Syalsabila; Gili Argenti (Jurnal Ilmiah Wahana Pendidikan, 2022)
One of the largest industrial cities, namely Karawang Regency, also experienced this. Therefore, the Karawang regency government is also thinking of an effort that is able to control the spread of covid 19 in industrial clusters, because the industrial cluster in Karawang Regency is the largest industrial cluster affected by the spread of covid 19. in this case the author is researching related to collaborative government in an effort to prevent the spread of covid 19 in the industrial sector in Karawang Regency in 2021. This research uses a descriptive qualitative approach and is coupled with Ansell and Gash's theory with 4 indicators, namely initial conditions, facilitative leadership, institutional design, and collaboration processes. In this study, it focuses on the efforts made by the Karawang Regency Government with government agencies related to the industrial sector to provide handling in tackling the spread of covid 19, besides explaining the role of private parties such as the Indonesian Company Association to help handle the problem of the spread of covid. the 19